Behavioral, Morphological, and Gene Expression Changes Induced by 60Co-γ Ray Irradiation in Bactrocera tau (Walker) - Cai, Jun; Yang, Hongxia; Shi, Song; Zhong, Guohua; Yi, Xin (Frontiers in Physiology, 2018)
The sterile insect technique (SIT) may reduce pest populations by allowing sufficient amount of irradiation-induced sterile males to mate with wild females whilst maintaining mating ability comparable to wild males. Although the SIT methods are well understood, the optimal sterilizing dose and processing development stage for application vary among species. To ensure effective pest control programs, effects of irradiation on physiology, behavior, and gene function in the target species should be defined, however, little is known about irradiation effects in Bactrocera tau. Here, the effects of irradiation on rates of fecundity, egg hatch, eclosion, mating competitiveness, flight capability, morphology of reproductive organs, and yolk protein (YP) gene expression were studied. The results showed that rates of female fecundity and egg hatch decreased significantly (51 ±19 to 0.06 ±0.06 and 98.90 ±1.01 to 0, respectively) when pupae were treated with > 150 Gy irradiation. Flight capability and mating competitiveness were not significantly influenced at doses < 250 Gy. Ovaries and fallopian tubes became smaller after irradiation, but there was no change in testes size. Finally, we found that expression of the YP gene was up-regulated by irradiation at 30 and 45 days post-emergence, but the mechanisms were unclear. Our study provides information on the determination of the optimal irradiation sterilizing dose in B. tau, and the effects of irradiation on physiology, morphology and gene expression that will facilitate an understanding of sub-lethal impacts of the SIT and expand its use to the control of other species.